Afforestation of Difficult Sites - Srivastava, T. N.; Qureshi, I. M. (Indian Forester, 1966)
The paper focusses attention on the urgent need for afforestation of ten major categories of difficult sites which pose problems to foresters in India. These are; (1) Shifting sand dunes in desert areas, (2) Saline and alkali soils, (3) Ravine lands, (4) Skeletal soils, murrumy soils, and rocky sites including denuded hill slopes, (5) Laterite and lateritic soils, (6) Coastal sea board, (7) Shallow and heavy black soils with or without lime concretions, (8) Cold deserts, (9) Water-logged areas, and (10) Littoral swamps or marshes, and raised mud flats. The characteristic features of each of the above types of areas have been described, together with the work done, difficulties experienced, species used and techniques followed. The extent of these areas is considerable as they total up to no less than 77 million hectares. Apart from the protective and ameliorative value of afforestation to these degraded sites, it is imperative to put these 1ands to productive purposes in view of the ever-increasing demand for firewood, timber and raw materials for wood-based industries in the country. This can be achieved on1y if a com.prehensive study of the edaphic, hydrological, ecological and silvicultural aspects of the problem is undertaken. This is being done at the Forest Research Institute, Dehra Dun, and the Central Arid Zone Research Institute, Jodhpur, in collaboration with the State Forest Departments.